Protective role of S-Adenosylmethionine against fructose-induced oxidative damage in obesity - Kameliya Zh Bratoeva; Mariya A. Radanova; Albena V. Merdzhanova; Ivan S. Donev (Journal of Mind and Medical Sciences)
Introduction. It has been shown that S-adenosylmethionine (S-AMe) stimulates glutathione synthesis and increases cell resistance to the cytotoxic action of free radicals and pro-inflammatory cytokines. The aim of this study was to determine the effect of Sadenosylmethionine on the oxidative stress in adipose tissue in a model of fructose-induced obesity. Methods. The study was performed on male Wistar rats divided into 3 groups: control, fructose fed (HFD) (35%, 16 weeks), and HFD + S-AMe (20 mg/kg). We examined the changes in the ratio of retroperitoneal adipose tissue weight / body weight; levels of reduced glutathione (GSH) and malondialdehyde (MDA) in the retroperitoneal adipose tissue, and serum levels of GSH and TNF-α. Results. Significant increases in the retroperitoneal adipose tissue, MDA, and serum TNF-α were identified, as well as decreased tissue and serum levels of GSH in rats fed with a high-fructose diet as compared with the control group. In the group fed with HFD and SAMe, we found significant reduction in the retroperitoneal adipose tissue and decreased levels of MDA and serum TNF-α, as well as increased tissue and serum levels of GSH as compared with the group only on HFD. In conclusion, our results show that fructose-induced obesity causes oxidative stress in hypertrophic visceral adipose tissue. The administration of S-AMe improves the antioxidative protection of adipocytes, and reduces oxidative damage and excessive accumulation of lipids and inflammation.